2022
DOI: 10.1177/20406223221109454
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and the risk of dementia based on an analysis of 396,332 participants

Abstract: Background: AMPK has attracted widespread interest as a potential therapeutic target for age-related diseases, given its key role in controlling energy homeostasis. Metformin (Met) has historically been used to treat Type 2 diabetes and has been shown to counteract age-related diseases. However, studies regarding the relationship between Met and a variety of age-related classifications of cognitive decline have reported mixed findings. Objective: To assess the potential effect of Met on the onset of dementia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(136 reference statements)
2
5
0
1
Order By: Relevance
“…Our findings were in line with previous studies indicating that metformin conferred a protective effect against dementia in people with T2D. 13,14,16,17,39 For instance, one national cohort study involving 210,237 showed that new users of metformin had a reduced risk of dementia compared to non-users, with an adjusted hazard ratio (HR) of 0.88 (95% CI, 0.84 −0.92). 16 Another retrospective cohort study involving 28,640 older veterans with T2D showed that metformin initiators had a lower risk of dementia than new users of sulfonylureas over an average follow-up of 5 years (HR, 0.89; 95% CI, 0.79 −0.99).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings were in line with previous studies indicating that metformin conferred a protective effect against dementia in people with T2D. 13,14,16,17,39 For instance, one national cohort study involving 210,237 showed that new users of metformin had a reduced risk of dementia compared to non-users, with an adjusted hazard ratio (HR) of 0.88 (95% CI, 0.84 −0.92). 16 Another retrospective cohort study involving 28,640 older veterans with T2D showed that metformin initiators had a lower risk of dementia than new users of sulfonylureas over an average follow-up of 5 years (HR, 0.89; 95% CI, 0.79 −0.99).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings were in line with previous studies indicating that metformin conferred a protective effect against dementia in people with T2D 13,14,16,17,39 . For instance, one national cohort study involving 210,237 showed that new users of metformin had a reduced risk of dementia compared to non‐users, with an adjusted hazard ratio (HR) of 0.88 (95% CI, 0.84 −0.92) 16 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5‐6). Of the 100 included reviews, 32 related diabetes to cognitive function in mixed diabetic populations, 2,6,8,26–54 seven examined the effect of type 1 diabetes, 3,55–60 19 focused on type 2 diabetes, 5,7,61–77 14 observed brain structure in diabetes, 1,4,78–89 two examined genetic and other biomarkers of dementia 90,91 and 26 focused on cognitive effects of antidiabetic treatment 14,15,20–22,92–112 . Of the 27 studies included in the meta‐analyses, 15 related metformin use to risk of dementia, 113–127 10 were used in the thiazolidinedione meta‐analysis, 113,122–130 four for pioglitazone, 126,129–131 seven for DPP‐4is, 123,125–127,132–134 five for α‐glucosidase inhibitors, 123,126,127,129,135 two for meglitinides, 126,129 seven for insulin, 122,123,125,127,129,136,137 11 for sulphonylureas,…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The incidence and prevalence of type 2 diabetes mellitus are high, particularly in developing countries such as China, 3 therefore the development of generic metformin hydrochloride (MH) tablets is urgently needed to fill the market gap created by the high demand for original metformin sustained-release tablets for patients with type 2 diabetes. 4,5 Recently, a growing number of studies have suggested benefits of the off-label use of metformin in different conditions, 6 such as the promotion of successful pregnancy in patients with polycystic ovarian syndrome with infertility due to anovulation, 7 weight loss, [8][9][10] cardiovascular protection, 11,12 breast and colorectal cancer, 13,14 glioblastoma, 15,16 amelioration of inflammation, 17,18 as a potential geroprotective agent for dementia, 19,20 and stimulation of hair growth. 21,22 These additional benefits of the off-label use of metformin exacerbate the mismatch between the supply and demand for the original drug.…”
mentioning
confidence: 99%